STUDI KORELASIONAL BOOKLET CERMAT DAN KEMAMPUAN BERNALAR KRITIS PADA PEMBELAJARAN AKIDAH AKHLAK DI MTs AL-IRSYAD MUNING BARU NEGARA - Liny Mardhiyatirrahmah (Al-Manba, 2026)
This study aims to determine the effect of using the CERMAT (Cerdas Belajar Menumbuhkan Akhlak yang Tepat) booklet on students' critical reasoning skills in Aqidah Akhlak learning at MTs Al-Irsyad Muning Baru Negara. This study employed a quantitative approach with a control group and an intervention group design. The research was conducted at MTs Al-Irsyad Muning Baru Negara. The instrument used was a questionnaire designed to measure students' critical reasoning skills before and after the learning process. The data obtained were analyzed using statistical tests to determine significant differences between the two groups. The analysis showed that the control group obtained a p-value of 0.074 (> 0.05), indicating that there was no significant effect on improving students' critical reasoning skills without the use of the CERMAT booklet. In contrast, the intervention group obtained a p-value of 0.012 (< 0.05), indicating a significant effect of using the CERMAT booklet on improving students' critical reasoning skills. These findings demonstrate that the CERMAT booklet, as an innovative learning medium, is able to provide positive stimulation, encouraging students to analyze, evaluate, and relate Aqidah Akhlak material to their everyday lives. The use of the CERMAT booklet significantly improved students' critical reasoning skills in learning Aqidah Akhlak. Engaging, systematic, and contextual learning media have great potential to enhance the quality of learning and support the achievement of educational goals more effectively and meaningfully.